Pengaruh Pemanfaatan Digital Marketing (Vidio Marketing, Website dan Sosial Media Marketing) terhadap Penerimaan Murid Baru dan Kepuasan Wali Murid - Fauzan, Alfu; Purwanti, Winaya (Universitas Negeri Makassar, 2025)
This study aims to analyze the influence of digital marketing, including websites, social media, and video marketing, on new student admissions and parent satisfaction. The study population was parents of kindergarten through high school students at Al-Marjan School. A sample of 100 parents was selected using purposive sampling, consisting of parents aged 25–50 years from all levels. The research method employed a quantitative approach, distributing questionnaires, and data were analyzed using Structural Equation Modeling (SEM) to test the partial and simultaneous effects of variables. The results indicate that partially, websites, social media, and video marketing have a positive effect on new student admissions, while websites, social media, and video marketing also significantly increase parent satisfaction. Video marketing plays a dominant role in attracting prospective students. Simultaneously, all three digital marketing variables contribute significantly to increasing new student admissions while strengthening parent satisfaction. These findings underscore the importance of an integrated digital marketing strategy for educational institutions to increase competitiveness, expand promotional reach, and build positive relationships with parents